The principles of sufism - Ba'uniyyah, A'ishah bint Yusuf -1516 or 1517 (Library of Arabic Literature, 2014)
The principles of sufism is a mystical guide book to help others on their spiritual path. Outlining the four principles of repentance, sincerity, remembrance, and love, it traces the fundamental stages of the spiritual novice's transformative journey, emphasizing the importance of embracing both human limitations and god's limitless love. Drawing on lessons and readings from centuries-old sufi tradition, A'ishah advises the seeker to repent of selfishness and turn to a sincere life of love. In addition to his lucid translation, Th. Emil Homerin provides an insightful introduction, notes and a glossary to A'ishah al-Ba'uniyyah's remarkable account of the pursuit of mystical illumination.